Appalachian Status Is a Negative Predictor of Breast Reconstruction Following Breast Cancer Resection. Issue 6 (December 2019) - DeCoster, Ryan C.; Stout, Megan A.; Burns, Jack C.; Shrout, Max A.; Wetzel, Margaret; Dugan, Adam J.; Rinker, Brian D.; Butterfield, Timothy A.; Webster, J. Matthew; Vasconez, Henry C.
Abstract : Background: Health care disparities in Appalachia are well documented. However, no previous studies have examined possible differences in the utilization of breast reconstruction (BR) in Appalachia. This study aims to determine if a disparity in BR utilization exists in women from Appalachia Kentucky. Methods: A retrospective, population-based cohort study was conducted from January 1, 2006, to December 31, 2015. The Kentucky Cancer Registry was queried to identify population-level data for female patients diagnosed with breast cancer and treated with mastectomy. A multivariate logistic regression model controlling for patient, disease, and treatment characteristics was constructed to predict the likelihood of BR. Results: Bivariate testing showed differences ( P < 0.0001) in BR utilization between Appalachian and non-Appalachian women in Kentucky (15.0% and 26.3%, respectively). Multivariate analysis showed that women from Appalachia (odds ratio, 0.54; confidence interval (95), 0.48–0.61; P < 0.0001) were less likely to undergo BR than non-Appalachian women. Interestingly, the rate of BR increased over time in both Appalachian ( r = 0.115; P < 0.0001) and non-Appalachian women ( r = 0.148; P < 0.0001). Conclusions: Despite the benefits of BR, women from Appalachia undergo BR at lower rates and are less likely to receive BR than non-Appalachian Kentuckians. Although the rates of BR increased over time in both populations, access to comprehensive breast cancer care remains a challenge for women from Kentucky's Appalachian region.